Western Mediterranean shelf-incised submarine canyons: multi-proxy evidence of Late Holocene natural and human-induced environmental changes - López-Quirós, Adrián; Puga-Bernabéu, Ángel; Lobo, Francisco José; Ruíz-Caballero, Elvira; Cerrillo-Escoriza, Javier; Pérez-Asensio, José N.; Mendes, Isabel; Mena, Anxo; Puche-Polo, Natalia; Alberjón-Peñas, Tomás; Wacker, Lukas (Frontiers in Earth Science, 2025)
Submarine canyons play a critical role in continental margin sediment transport, functioning both as sediment traps and conduits. This study examines the depositional dynamics of the Motril, Carchuna, and Calahonda canyons in the northern Alboran Sea (western Mediterranean) to assess their role in Holocene sediment storage and transfer. Comprehensive sedimentological and elemental geochemical analyses reveal distinct sedimentation patterns driven by geomorphology, diverse transport mechanisms, and hydroclimatic variability. The Motril Canyon primarily functioned as a river-fed sediment trap, accumulating fine-grained terrigenous material from the Guadalfeo River. At the same time, the Carchuna Canyon was dominated by longshore drift and turbidity currents mobilizing coarse-grained sediments. In contrast, the Calahonda Canyon displays an intermediate behavior, influenced by alongshore drift and fluvial inputs. The Late Holocene sedimentary record from the Motril Canyon provides a high-resolution sedimentary archive of paleoenvironmental changes over the last ∼2000 years Current Era, reflecting both climatic variability and human-induced landscape alterations. Four phases are identified based on the relationships between sediment physical and mineral-chemical characteristics: the Iberian Roman Humid Period (2600–1600 cal. yr Before Present), characterized by diminished terrigenous input despite increased late-phase humidity; the Dark Ages (1500–1000 cal. yr BP), marked by elevated sedimentation linked to soil erosion and intensified land use; the Medieval Climate Anomaly (1050–650 cal. yr BP), where persistent fine-grained deposition was driven largely by anthropogenic land degradation; and the Little Ice Age (650–150 cal. yr BP), which witnessed heightened sedimentation due to increased rainfall and river discharge. A decline in fluvial-derived material during the Industrial Period indicates a shift towards overall drier conditions, associated with changes in precipitation patterns and land use. These findings underscore the interplay between natural climatic fluctuations and human activities influencing western Mediterranean margin sedimentation. While the Motril Canyon does not serve as a direct conduit to deep waters, it nonetheless records the progressive aridification and anthropogenic impacts experienced in southern Iberia. Furthermore, the contrasting sediment dynamics observed in the Carchuna and Calahonda canyons highlight the inherent complexity of shelf-to-slope sediment transfer. This complexity underlines the necessity to consider human influences when interpreting Late Holocene paleoenvironmental records.